2023
DOI: 10.1093/ecco-jcc/jjad204
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dietary Interventions on the Microbiota in Inflammatory Bowel Disease: A Systematic Review

Cheenie Nieva,
Jennifer Pryor,
Georgina M Williams
et al.

Abstract: Background and Aims Diet plays an integral role in the modulation of the intestinal environment, with the potential to be modified for management of individuals with inflammatory bowel disease (IBD). It has been hypothesised that poor “Western-style” dietary patterns select for a microbiota that drives IBD inflammation and that through dietary intervention, a healthy microbiota may be restored. This study aimed to systematically review the literature and assess current available evidence rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Ulcerative colitis (UC), mainly associated with chronic inflammation and ulceration of the colon, is a significant risk factor for the development of colorectal cancer [ 6 ]. Different studies have found that UC patients who consume a high-fiber, low-fat diet show reduced inflammation and microbial dysbiosis [ 7 , 8 ]. Although the intestinal microbiota is sensitive to different environmental cues (including diet, stress, medications, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC), mainly associated with chronic inflammation and ulceration of the colon, is a significant risk factor for the development of colorectal cancer [ 6 ]. Different studies have found that UC patients who consume a high-fiber, low-fat diet show reduced inflammation and microbial dysbiosis [ 7 , 8 ]. Although the intestinal microbiota is sensitive to different environmental cues (including diet, stress, medications, etc.)…”
Section: Introductionmentioning
confidence: 99%